Arabidopsis ADF1 is Regulated by MYB73 and is Involved in Response to Salt Stress Affecting Actin Filament Organization. (4th June 2021) - Wang, Lu; Qiu, Tianqi; Yue, Jianru; Guo, Nannan; He, Yunjian; Han, Xueping; Wang, Qiuyang; Jia, Pengfei; Wang, Hongdan; Li, Muzi; Wang, Che; Wang, Xianling
Abstract: Actin cytoskeleton and transcription factors play key roles in plant response to salt stress; however, little is known about the link between the two regulators in response to salt stress. Actin-depolymerizing factors (ADFs) are conserved actin-binding proteins in eukaryotes. Here, we revealed that the expression level of ADF1 was induced by salt stress. The adf1 mutants showed significantly reduced survival rate, increased percentage of actin cable and reduced density of actin filaments, while ADF1 overexpression seedlings displayed the opposite results when compared with WT under the same condition. Furthermore, biochemical assays revealed that MYB73, a R2R3 MYB transcription factor, binds to the promoter of ADF1 and represses its expression via the MYB-binding site core motif ACCTAC. Taken together, our results indicate that ADF1 participates in salt stress by regulating actin organization and may also serve as a potential downstream target of MYB73, which is a negative regulator of salt stress.